Identification of microRNA biomarkers for response of advanced soft tissue sarcomas to eribulin: Translational results of the EORTC 62052 trial. (April 2017) - Wiemer, Erik A.C.; Wozniak, Agnieszka; Burger, Herman; Smid, Marcel; Floris, Giuseppe; Nzokirantevye, Axelle; Sciot, Raf; Sleijfer, Stefan; Schöffski, Patrick
Abstract: Background: Recent phase II and III clinical trials demonstrated anti-tumour activity of eribulin, a tubulin-interacting cytotoxic agent, in patients with metastatic soft tissue sarcoma (STS). In this exploratory study, we aimed to identify putative microRNA biomarkers that associate with eribulin sensitivity or resistance in STS. Materials and methods: Archival tumour tissue from primary tumours or metastatic lesions was collected prior to eribulin treatment, from 65 consenting patients involved in the EORTC trial 62052. This phase II study (ClinicalTrials.gov identifierNCT00413192 ) included multiple subtypes of STS. Tissue was available from 21 leiomyosarcomas, 14 adipocytic sarcomas, 9 synovial sarcomas and 21 other sarcoma histotypes. Total RNA was isolated from formalin-fixed, paraffin-embedded tumour samples and analysed using Taqman ® Low Density Arrays to determine microRNA expression profiles. The expression of a total of 756 microRNAs was assessed. Progression-free survival at week 12 (RECIST 1.0) measured as a binary variable, was the primary end-point of the clinical trial and used as a primary response measure for correlative studies. Seventeen of 53 (32.1%) evaluable patients in the analysed subset had non-progressive disease at week 12 and were defined as responders. Results: The expression of 26 individual microRNAs (p < 0.05) differed significantly between non-responders and responders. Additional microRNAs of potential relevance were identified when considering the different histological subgroups. Conclusions: The expression level of particular microRNAs in STS tissue samples may predict response to eribulin. Further validation studies as well as a preclinical assessment of the underlying molecular mechanisms are required. Highlights: Differentially expressed microRNAs (miRNAs) in STS are found in eribulin responders/non-responders. MicroRNA expression levels in soft tissue sarcoma (STS) may predict response to eribulin. miRNA expression identifies different STS subtypes.